The contribution to success of various methods of treatment of temporomandibular joint ankylosis (a statistical study containing 24 cases) - Tanrikulu, Rezzan; Erol, Behçet; Görgün, Belgin; Söker, Murat (The Turkish Journal of Pediatrics, 2005)
Temporomandibular joint (TMJ) ankylosis is an important joint disorder which, in addition to emerging through trauma, can also arise as a result of local and systemic infections. TMJ ankylosis which develops in childhood in particular has its own characteristics. Despite the existence of different views on the treatment of TMJ ankylosis, various techniques have been defined, and three basic techniques are currently employed: gap arthroplasty, interpositional arthroplasty and joint reconstruction. Our study is intended as a statistical inquiry into the contribution to the operation success of the three different methods of treatment. Moreover, the effect on treatment outcome of unilateral or bilateral ankylosis is also statistically evaluated. In our study, eight cases were treated with gap arthroplasty, nine with interpositional arthroplasty and seven with joint reconstruction performed by costochondral graft. As a result of our statistical evaluation, it was determined that the effect of interpositional arthroplasty on post-operative maximal interincisal mouth opening was greater than that observed with the other methods.